Reconstructing village spatial layout to achieve rural revitalization: a case from a typical township in China - Zhu, Zhiyuan; Wang, Huaizhou; Yang, Jihao; Feng, Yongzhong (Frontiers in Sustainable Food Systems, 2023)
Rural revitalization is a strategy proposed by China to solve the imbalance and insufficiency of urban and rural development. The purpose of village system reconstruction is to optimize the rural spatial structure and realize the efficient allocation of resource elements, which is of great significance to the overall revitalization of rural areas. This research adopts the analytic hierarchy process, the multiindex comprehensive evaluation method ,and GIS spatial analysis, taking Zhiyang Town as a case, reconstructing the indexes selection of village level system, putting forward a set of complete classification system, through selecting village scale, resource conditions, social economic development level and industry and other related data index, build a village level system of evaluation system, The 25 villages in Zhiyang Town were divided into four classes. Different development paths are proposed for different levels of villages. The evaluation of the village development level and reconstruction path of the village hierarchy system has certain practical guiding value for rural construction, which is of great significance for the realization of rural revitalization.